Educagao fisica escolar e sedentarismo infantil: Uma analise comportamental' - Orti, Natalia Pinheiro [UNESP]; Carrara, Kester [UNESP] (My University, 2012)
There have been many researchers dedicating themselves to analyze behavior to get solutions to social problems. The practice of childhood sedentary lifestyle is a complex problem that evokes a public health concern. This article exposes a work field in which researches identify, describe and analyze verbal reports about effective contingencies at school. It introduces the practices of three teachers of physical education and their 62 students. The results suggest that actions that can support public policies toward mitigating health risks.
childhood sedentary lifestryle and physical education at school: A behavioral analysis
Keywords: Child sedentariness; Cultural behavior analysis; Physical education at school